Harnessing molasses as a low-cost carbon source for production of poly-hydroxy butyrate (PHB) using Burkholderia sp. B73 bacteria - Diah - RATNANINGRUM; Een Sri ENDAH; Puspita LISDIYANTI; Sri PRIATNI; Vienna SARASWATY (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2021)
Burkholderia sp. has been reported as a poly-hydroxy-butyrate (PHB) producer. PHB is a natural polyester class with a wide range of applications in foods, medicines, and biomedicines. However, the high production cost of PHB may limit its potential. Molasses, a by-product of the sugarcane industry available abundantly, may be used as an alternative carbon source of PHB production. In this research, we aimed to evaluate PHB production by Burkholderia sp. B73 in fermentation media using molasses as an alternative carbon source. Small-scale experiments were performed in Erlenmeyer flasks on a shaker at 150 rpm and 30 °C to evaluate the best initial C/N ratio for biomass accumulation and PHB production. A set of parameters including bacterial growth, dry cell weight, yield, and FTIR spectrum of PHB were observed. The results showed that molasses could be used to grow Burkholderia sp. B73 and the highest PHB production was obtained when a 20:1 C/N ratio of molasses was applied in the fermentation medium. In addition, when the initial pH was adjusted to 7.0, the highest PHB yield was also produced. More importantly, the use of molasses as a carbon source improved the PHB yield by nearly 2-fold compared with our previous report using a synthetic Ramsay’s minimal medium. In conclusion, the experiment results showed that molasses could be used as a low-cost carbon source for PHB production by Burkholderia sp. B73 bacteria.